Highly efficient exciplex organic light-emitting devices employing a sputtered indium-tin oxide electrode with nano-pinhole morphology. Issue 46 (7th November 2017) - Lee, Chih-Chien; Shih, Chun-Jen; Kumar, Gautham; Biring, Sajal; Sen, Somaditya; Liu, Shun-Wei
Abstract : An exciplex-forming phosphorescent OLED with nano-pinhole sputtered ITO exhibiting a maximum external quantum efficiency (power efficiency) of 34% (132.8 lm W −1 ) was achieved. Abstract : We propose a DC sputtering process to fabricate an indium-tin oxide (ITO) electrode with nano-pinhole morphology for an efficient exciplex organic light-emitting device (OLED). The ITO thin-film of 80 nm thickness sputtered at room temperature shows an optical transmittance of over 86.5% in the range of visible light and an electrical sheet resistance of 75 ohm sq −1 . A layer of di-[4-( N, N -ditolyl-amino)-phenyl]cyclohexane (HATCN) is inserted into the device to improve the hole injection efficiency by reducing the injection barrier at the anode/di-[4-( N, N -ditolyl-amino)-phenyl]cyclohexane (TAPC) interface and simultaneously modifying the work function of sputtered ITO/HAT-CN to 5.5 eV, as characterized by photoelectron spectroscopy. The exciplex-forming phosphorescent OLEDs employing such sputtered ITO exhibit a maximum external quantum efficiency, power efficiency, and current efficiency of 34%, 132.8 lm W −1, and 127.6 cd A −1, respectively. In addition, the device shows Lambertian emission attributed to the sputtered ITO film with a special nano-pinhole morphology by enhancing the scattering effect inside the device and resulting in the improvement of the light extraction properties and device performance.